Modification of ITU-R Parameters to Improve the Prediction of Tropospheric Scintillation for Tropical Regions - Philip B, John; K Kotamraju, Sarat; Sri Kavya, Ch (International Journal of Engineering and Technology, 2018)
Scintillation is the rapid fluctuation of the received signal. It is caused by the variation in the refractivity structure of the atmosphere profile. This phenomenon leads to the signal degradation and is significant in low fade margin links and at low elevation angles. So, analyzing the scintillation intensity and its statistics are vital for a system designer to design an efficient system for the satellite communication link. This paper presents the methodology to extract the scintillation intensity from the raw beacon signal and comparison of ITU-R scintillation prediction model with the measured results to test its acceptability over tropical region. When compared with measured results, ITU-R model overestimates the scintillation fade. Hence the parameters of the time percentage factor are modified to obtain near fit to the measured results.